Sickle cell disease in pregnancy. Issue 3 (March 2019) - Rogers, Kanda; Balachandren, Neerujah; Awogbade, Moji; Johns, Jemma
Abstract: Sickle cell disease (SCD) is a chronic, multisystem disease. Despite decades of medical advances in SCD management, studies have revealed an increased risk of stillbirth, preterm delivery, small for gestational age, maternal mortality and preeclampsia, compared to the general population. Pregnant women with SCD should be cared for within the multidisciplinary team, comprised of specialist obstetricians, high risk midwives and haematologists. A national confidential enquiry into patient outcomes and death (NCEPOD), expressed concerns with a lack of consistent care for SCD patients in pregnancy. Within the UK, there is great geographical variation in the prevalence of SCD, with the highest incidence in large urban, multicultural centres. Trainee obstetricians practising outside of these areas may not gain substantial experience in managing these patients: therefore this review aims to highlight the key antenatal, intrapartum and postnatal elements involved in managing pregnant women with SCD.